Characterising the nutritional status of children with primary ciliary dyskinesia. Issue 5 (October 2019) - Marino, L.V.; Harris, A.; Johnstone, C.; Friend, A.; Newell, C.; Miles, E.A.; Lucas, J.S.; Calder, P.C.; Walker, W.T.
Summary: Introduction: Primary ciliary dyskinesia (PCD) is a rare, heterogeneous genetic disorder where impaired mucociliary clearance is caused by dysfunctional motile cilia leading to bronchiectasis. There is limited evidence characterising the nutritional status of children with PCD, although lower body mass index (BMI) z-score has been associated with worse lung function (FEV1 ). Methods: All children (n = 43) with PCD, aged <16 years, from a single tertiary centre were prospectively enrolled. Information on clinical phenotype and nutritional status including bioelectrical impedance spectroscopy (BIS) phase-angle was collected. Results: There was a weak positive association between height-for-age z-score (HAZ) and FEV1 z-score (n = 28, r = 0.4, p = 0.049). Those with a low fat free mass index (<-2 z scores) had a lower BMI z score (−1.3 ± 1.2 vs. 0.8 ± 0.7, p = 0.0002). BIS phase angle identified more patients at nutritional risk than using moderate malnutrition cut-offs of either HAZ or BMI ≤ -2 z scores alone (21% vs. 4.6% vs. 6.9% respectively). PCD patients had a higher incidence of vitamin D insufficiency (<50 nmoL/L) (54%) and deficiency (<30 nmoL/L) (26%) than healthy children. Conclusions: We have characterised the nutritional phenotype of a cohort of children with PCD. Monitoring vitamin D levels is important in PCD patients. There is a weak association between lung function and nutritional status, and measures of BIS phase-angle. The use of BIS phase-angle may allow for early identification of at risk children and may therefore be of benefit for nutritional assessments in the clinical setting. These findings will help inform a future nutritional intervention strategy in children with PCD.